2017
DOI: 10.1021/acs.jctc.7b00388
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Molecular Dynamics Simulations of Polaritonic Chemistry

Abstract: When photoactive molecules interact strongly with confined light modes as found in plasmonic structures or optical cavities, new hybrid light-matter states can form, the so-called polaritons. These polaritons are coherent superpositions (in the quantum mechanical sense) of excitations of the molecules and of the cavity photon or surface plasmon. Recent experimental and theoretical works suggest that access to these polaritons in cavities could provide a totally new and attractive paradigm for controlling chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
223
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(225 citation statements)
references
References 82 publications
2
223
0
Order By: Relevance
“…Polaritonic chemistry has become an emerging research field, aimed at providing new tools for the fundamental investigation of light-matter interaction. Since the pioneering experimental work carried out by the group of Ebbesen, in which they observed that strong light-matter coupling could modify chemical landscapes [8], the field of 'molecular polaritons' experienced much activity from both experimental [9][10][11][12][13][14][15][16][17][18][19] and theoretical [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] research groups. Recent achievements on molecules strongly coupled to a cavity mode, such as that strong cavity-matter coupling can alter chemical reactivity [9,38], provide long-range energy or charge transfer mechanisms [12,37], modify nonradiative relaxation pathways through collective effects [35], and modify the optical response of molecules [31,40], support the relevance of such a new chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Polaritonic chemistry has become an emerging research field, aimed at providing new tools for the fundamental investigation of light-matter interaction. Since the pioneering experimental work carried out by the group of Ebbesen, in which they observed that strong light-matter coupling could modify chemical landscapes [8], the field of 'molecular polaritons' experienced much activity from both experimental [9][10][11][12][13][14][15][16][17][18][19] and theoretical [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] research groups. Recent achievements on molecules strongly coupled to a cavity mode, such as that strong cavity-matter coupling can alter chemical reactivity [9,38], provide long-range energy or charge transfer mechanisms [12,37], modify nonradiative relaxation pathways through collective effects [35], and modify the optical response of molecules [31,40], support the relevance of such a new chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Describing the photon-matter interaction with the tool of cavity quantum electrodynamics is an emerging field. It has been successfully demonstrated both experimentally [26][27][28][29][30][31][32] and theoretically [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], that the quantized photonic mode description of the electromagnetic field can provide an alternative solution for studying adequately the light-molecule's OPEN ACCESS RECEIVED…”
mentioning
confidence: 99%
“…Nonadiabatic molecular dynamics combined with machine‐learning strategies for the calculation of electronic‐structure quantities has recently emerged . Quantum electrodynamics effects have been introduced in nonadiabatic dynamics to investigate, for example, molecular dynamics in an optical cavity or the description of stimulated emission processes …”
Section: Discussionmentioning
confidence: 99%